4. Using Administrative Data to Study Persons with Disabilities - Iezzoni, Lisa I. (The Milbank quarterly, 2002)
Administrative data are the by‐product of running the health care system: enrolling people in health plans, tracking service utilization, paying claims, and monitoring costs and quality. Although not originally intended for conducting research, administrative data offer significant advantages: • They encompass large groups of people, often entire populations (such as all residents of a state), thus enhancing the generalizability of research findings. • They represent care practiced throughout the community and are not confined to restricted settings. • Longitudinal, person‐level, administrative databases can track study subjects over time and across settings of care. • Large numbers of cases help hide individual identities; furthermore, researchers generally conduct studies without knowing the specific identities of the research subjects, thus protecting confidentiality. • They already exist, are relatively inexpensive to acquire, and are computer readable. Administrative data result from administering health plans‐‐‐tracking service utilization, paying claims, monitoring costs and quality‐‐‐and have been used extensively for health services research. This article examines the strengths and limitations of administrative data for health services research studies of people with disabilities. Administrative data offer important advantages: encompassing large populations over time, ready availability, low cost, and computer readability. Questions arise about how to identify people with disabilities, capture disability‐related services, and determine meaningful health care outcomes. Potentially useful administrative data elements include eligibility for Medicare or Medicaid through Social Security disability determinations, diagnosis and procedure codes, pharmacy claims, and durable medical equipment claims. Linking administrative data to survey or other data sources enhances the utility of administrative data for disability studies.